Tratamento Endovascular de Patologia da Aorta Torácica Descendente na Síndrome de Marfan: Revisão Sistemática - Ana Rita da Silva Rodrigues (2021)
Introduction: Marfan Syndrome (MFS) is associated with progressive aortic degeneration with the risk of potentially fatal complications. The evolution in medical and surgical treatment has contributed to a substantial increase in life expectancy. However, it has led to an increasing number of complications in other aortic segments, with the need for multiple reinterventions. Considering the morbidity and mortality associated with a rising number of surgical interventions in this subset of patients, thoracic endovascular aortic repair (TEVAR) has emerged as a promising alternative to open surgery. Objective: This systematic review aims to evaluate short, medium and long-term outcomes of TEVAR for treatment of descending thoracic aortic disease in MFS and to assess the risk/benefit of the endovascular approach. Methods: The PubMed, Web of Science and Scopus databases were consulted between August 2020 and January 2021, and all reporting results of MFS patients with descending thoracic aortic aneurysms (dTAA) or type B aortic dissection (TBAD) who underwent TEVAR were identified. Reported outcomes were categorized as (primary endpoints): primary treatment failure; secondary treatment failure; and successful treatment. It was also analyzed the incidence of treatment-related complications, namely: endoleak, neurological morbidity, aortic rupture, anterograde false lumen expansion, retrograde type A aortic dissection (rTAD), death and the need for re-intervention. Results: A total of 16 studies which fulfilled the eligibility criteria were identified, making a sample of 119 patients. The procedure was performed in an elective setting in 77 patients and the remaining 36 were treated in an urgent/emergent setting. The mean age was 41,10±13,05 years. Successful treatment was achieved in 48,73%, with a significant rate of primary (41.18%) and secondary (7.56%) treatment failure. Mean follow-up period was 28,61±27,84 months. We identified endoleaks in 18,49% of patients (86,4% type I), anterograde false lumen expansion in 12,61%, rTAD in 4,20% and aortic rupture in 4,20%. The incidence of perioperative neurological events was 3,16% and early and late mortality was 5,88% and 10,08%, respectively. A new endovascular procedure was needed in 14 cases and conversion to open surgery occurred in 21. Conclusions: The use of TEVAR in MFS is associated with lower short-term morbidity and mortality rates than open surgery. However, it has a higher medium-term mortality rate. Nevertheless, we recommend the use of TEVAR solely in patients judged to be at prohibitive risk for open surgery or as a bridge to a definite open repair in an emergency setting, in which rapid stabilization is required. Technical expertise and close postinterventional surveillance are mandatory to minimize device and aorta-related complications.